Identifikasi Jenis Resort Di Sumatera Utara Melalui Website Resort: Studi Kasus Simalem Resort Dan Mariana Resort - Akmal, Rifki; Anastassya, Arimbi; Harpan, Jhodil Khoir; Shanorra, Tania Tita; Hanafi, M. Imam; Chaidir, Muhammad (JURNAL BISNIS HOSPITALITI, 2025)
North Sumatra has excellent tourism potential, one of which is Lake Toba, which is included in the 10 National Priority Tourism Destinations. To support tourism development, quality accommodation is an important factor, including resorts that offer exclusive experiences for tourists. Two well-known resorts in the Lake Toba area are Marianna Resort and Simalem Resort. This study aims to compare the two as a reference for property developers in developing new resorts. This study uses a qualitative description method with 3A analysis (Attractions, Amenities, and Accessibility). Data were obtained through observation of the official websites of the two resorts and a literature review from the book "Tourism Planning: An Integrated Sustainable Development Approach" by Edward Inskeep. The results of the study show that both resorts have zone classifications based on the Tripartite Concept method, namely core zones, buffer zones, and service zones, with different characteristics in supporting the tourism experience. The conclusion of this study reveals that design strategies greatly influence the attractions and amenities offered. Resorts that have been operating for a long time need to update their facilities to stay competitive. Providing diverse attractions and complete amenities is key to creating an exclusive experience for visitors. This study is expected to be a reference for developers in designing innovative and sustainable resorts on Lake Toba.